Obesity as a form of malnutrition: over-nutrition on the Uganda “malnutrition” agenda - Ngaruiya, Christine; Alison, Hayward; Lori, Post; Mowafi, Hani (Pan African Medical Journal, 2017)
The objectives were to highlight the burden of overweight and obesity as an additional area of importance for the malnutrition agenda in Uganda and to provide evidence-based considerations for stakeholders involved. Introduction: Mirroring other Low- and Middle-Income Countries (LMICs), Uganda is experiencing a "double burden" of over-nutrition related issues - both obesity and overweight, and related non-communicable diseases (NCDs) alongside the under-nutrition that has long plagued the country. Despite the commonplace assumption that under-nutrition is the predominant form of malnutrition in Uganda, we explore recent literature that in fact, challenges this notion. While food insecurity has contributed to the under-nutrition problem, a lack of dietary diversity also has a demonstrated role in increasing over-nutrition. We cannot afford to ignore over-nutrition concomitant with stunting and wasting in the country. Increase in the burden of this less acknowledged form of malnutrition in Uganda is critical to investigate, and yet poorly understood. A move towards increased regionally targeted over-nutrition research, funding, government prioritization and advocacy is needed.